Rectangular Porous-Core Photonic-Crystal Fiber With Ultra-Low Flattened Dispersion and High Birefringence for Terahertz Transmission - Zhang, Yani; Jing, Xin; Qiao, Dun; Xue, Lu (Frontiers in Physics, 2020)
We propose a novel porous-core photonic crystal fiber (PCF) consisting of asymmetrical rectangular air holes in the core and six-ring hexagonal lattice circular air holes in the cladding for achieving low-loss polarization terahertz transmission in a wide frequency range. By assuming TOPAS as the host material, the finite element method (FEM) is used to investigate its properties. The near-zero flattened dispersion of −0.01±0.02 ps/THz/cm is achieved over a frequency range of 1.0–2.0 THz, as well as a high birefringence of 7.1 × 10−2 which can be useful for polarization-maintaining applications. Also, critical parameters such as mode field distribution, effective material loss, confinement loss, and effective mode area are discussed in detail. Further, fabrication possibilities are discussed briefly by comparing recent work on similar waveguide structures. OCIS Codes: 040.2235 (Far infrared or terahertz), 060.4005 (Micro-structured fibers), 060.2420 (Fibers, polarization-maintaining), 160.5470 (Polymers).